Breath of the World in Legal Method Doctrine During Interwar Period in Latvia. Vassily Sinaisky’s Scientific Heritage Review - Apse, Diāna (Journal of the University of Latvia. Law, 2018)
The article contains the analysis of several aspects of Professor Vassily Sinaisky’s scientific, practical and academic work, such as folklore as a legal heritage, the search for the content of justice and legal norm, preparation of the new generation of scientists and, especially, the research dedicated to legal methodology. “Legal methodology technique in relation to the general doctrine about methodology” is based on the practical course of legal science methodology lectured at the University of Latvia over the course of 20 years, which back then was a rarity in West European universities. In this book, he highlights the fact that he has shown the legal methods, their terms of use for a conducting proper research and the achievement of successful outcome. These terms are both simultaneously a technique and an art. In this work, the legal historical methods are analysed with regard to the general aspects of sources, comparison, reconstruction, etc. Besides, the book covers dogmatic rulemaking and legal comprehension methods – court, scientific and pedagogic ones. In the conclusion, the author proposes a new research subject: topics, problematic, systematics as a subject of the general legal method and in relation to the modern age requirements, especially civil rights. The number of the professor’s publications during his scientific activity in Latvia is 96, including 16 publications about legal methodology. The professor’s conclusions and the revealed content of legal methods can still be used in studies, research and practice.